Comparation Study Performance Diesel Engine Using Biodiesel with Secondary Data. Issue 1 (December 2020) - Muhammad Febriansyah, Iqbal; Riza, Abrar; Darmawan, Steven
Abstract: Biodiesel is one of the diesel engine fuels with a mixture of fossil fuels with the addition of vegetable oil fuels. Biodiesel is expected to compete with other fossil fuels. The purpose of this research is to get a trend in the performance of Diesel engines by using biodiesel against fossil fuels so as to obtain the characteristics of biodiesel fuels. Conduct a comparative study of each different type of biodiesel. Get an upward or downward trend in biodiesel fuels against fossil fuels so as to obtain the characteristics of biodiesel fuels. Diesel engine performance that is concerned is torque, power, specific fuel consumption. The best diesel engine performance requirements are torque value, power and specific fuel consumption decreases. The method of data collection is done using secondary data from the results of previous studies that have been published. This research uses palm oil, jatropha curcas oil, calophyllum inophyllum oil, gossypium arboretum oil, brassica napus oil, and hevea brasiliensis oil. The best Diesel engine performance is found in B25 jatropha curcas oil biodiesel with an increase in torque value of 6.49%, an increase in power value of 6.49%, and a decrease in the value of specific fuel consumption by 17.78%.